Controversy Between In Vitro Biological Activities of a Novel Designed Antimicrobial Peptide and Its In Silico Predicted Activities: Novel in silico designed AMP - Fathi , Fariba; Ghobeh , Maryam; Mahboubi, Arash; Tabarzad, Maryam (Trends in Peptide and Protein Sciences, 2022)
Due to their unique mechanisms of action, antimicrobial peptides (AMPs) are promising candidates to combat different infectious diseases. They usually non-specifically interact with the bacterial cell membrane, create pores in their membrane and increase its permeability which causes the death of pathogens. In the design and development of AMPs, in silico strategies have been developed to enhance the function and activity of natural peptides. In this study, in silico approaches were used to develop a novel AMP with several extra bioactivities. Then, the designed AMP were analyzed through computational methods by in vitro experiments. Bioinformatics research revealed a 10-amino-acid peptide (LVSARIRCPK) having antibacterial, anti-biofilm, antiviral, antifungal, and anti-inflammatory effects. However, only the antiviral capabilities of the peptide were validated in the experimental analysis of antibacterial, antifungal, and antiviral activities. This data suggests that; while bioinformatics approaches have greatly advanced in recent years, more optimization work has to be done in order to attain high accuracy and minimize mistakes. HIGHLIGHTS A novel 10 residues anti-microbial peptide was designed using bioinformatics tools. In vitro analysis showed that this novel AMP did not have efficient antimicrobial activities. Stringencies of bioinformatics criteria thresholds setting may result in better design.